2022
DOI: 10.1002/hbm.26120
|View full text |Cite
|
Sign up to set email alerts
|

The increased inter‐brain neural synchronization in prefrontal cortex between simulated patient and acupuncturist during acupuncture stimulation: Evidence from functional near‐infrared spectroscopy hyperscanning

Abstract: The patient–acupuncturist interaction was a critical influencing factor for acupuncture effects but its mechanism remains unclear. This study aimed to examine the inter‐brain mechanism of patient–acupuncturist dyad during acupuncture stimulation in a naturalistic clinical setting. Seventy healthy subjects (simulated “patients”) were randomly assigned to two groups and received verum acupuncture group or sham acupuncture by one acupuncturist. Functional near‐infrared spectroscopy hyperscanning was used to simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Consistent with the study of Chen et al [13], our GCA result found no differences in IBS direction between the informer and guesser in the couple group. The result may be due to the specificity of the face-to-face deception task, which differed from other social interactions, such as instructor-learner [52] or gesturer-guesser interactions [88], indicating that there were no roles of 'leader' and 'follower' in the interaction, and several previous hyperscanning studies have reached the same conclusion [28,89,90]. This balance can be seen as the synchroneity and equal effort of making inferences about the partner's mental state.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with the study of Chen et al [13], our GCA result found no differences in IBS direction between the informer and guesser in the couple group. The result may be due to the specificity of the face-to-face deception task, which differed from other social interactions, such as instructor-learner [52] or gesturer-guesser interactions [88], indicating that there were no roles of 'leader' and 'follower' in the interaction, and several previous hyperscanning studies have reached the same conclusion [28,89,90]. This balance can be seen as the synchroneity and equal effort of making inferences about the partner's mental state.…”
Section: Discussionmentioning
confidence: 92%
“…During the Toutianliang reducing method, the bilateral PFC and primary MC were activated, and the FC between the left PFC and primary MC increased; however, the differences between the two reinforcement methods were not significant. In addition, Chen L. et al (2023) found that even during reinforcing-reducing manipulation with the lifting-thrusting method at the Quchi point, the frontal lobe cortex of the participant and the acupuncturist revealed increased inter-brain neural synchronization, which was related to the participant’s acupuncture sensation. Different reinforcing and reducing methods at the same acupoint can have opposite effects, and the difference of cortical response displayed by fNIRS may be the central mechanism leading to different clinical effects.…”
Section: Resultsmentioning
confidence: 98%
“…The absorption of near-infrared light was measured at the wavelengths of 785 and 830 nm and the sampling frequency was 3.91 Hz. Same as our recent study (Chen et al, 2022), the sensorimotor cortex (SMC) and prefrontal cortex (PFC) was selected as The fNIRS optode was placed according to the international 10-10 EEG system (Tsuzuki et al, 2017), with Fpz and Cz as reference points. The separation distance of sources and detectors was set to 2.5-3 cm.…”
Section: Fnirs Data Acquisitionmentioning
confidence: 99%